ChemInform Abstract: An Overview of Recent Electrochemical Immunosensing Strategies for Mycotoxins Detection. Issue 38 (September 2016) - Catanante, Gaelle; Rhouati, Amina; Hayat, Akhtar; Marty, Jean Louis
Abstract: Review: [97 refs.